Metformin as a medicine decreasing cardiovascular risk in patients suffering from type 2 diabetes mellitus - Wieteska, Małgorzata; Kaczyńska, Agnieszka; Maj, Dominik; Stanicki, Paweł; Chałupnik, Aleksandra; Wójcik, Piotr (Journal of Education, Health and Sport, 2020)
Almost half of deaths in Poland (approximately 49%) are caused by cardiovascular system diseases. It means that in 2018 it contributed to the death of over two hundred thousand people in our country. Myocardial infarction, stroke and heart failure are the most common of cardiovascular diseases (CVD). The main risk factor for progression of cardiovascular diseases is type 2 diabetes mellitus (T2D). It is estimated that almost 3 million people suffer from T2D in Poland. Metformin is a promising medicine that reduces cardiovascular risk in patients with T2D. It is currently used as the first line drug in patients suffering from T2D. The aim of the presented article is to review current research on the effectiveness of the metformin as a medicine that reduces cardiovascular risk in patients with T2D. Metformin is the oldest and most commonly used medicine that reduces the concentration of glucose in the peripheral blood in patients with T2D. Due to its very good safety profile, low cost and high effectiveness, metformin is used in the first-line treatment for T2D. Recent studies indicate its protective effect by vasodilation, reducing the size of myocardial infarction, inhibiting apoptosis of cardiomyocytes or reducing oxidative stress. Currently, metformin can be seen to have a great potential in the treatment of cardiovascular complications occurring in the course of T2D. Despite the fact that this medicine has been on the market for many years, the studies on its cardioprotective effects have been carried out for a relatively short period of time. It is possible that the detailed understanding of all mechanisms of action of metformin will lead to future advances in the treatment of not only T2D, but also cardiovascular and cancer diseases.